Síntese e caracterização de substratos vítreos para a obtenção de nanopartículas metálicas e aplicação na redução de nitrofenóis - Locatelli, Poliane Patricia Pelisão (2018)
Glass systems based on boron and phosphorus compounds allow the obtaining of self-supported metallic nanoparticles on their surface when doped with transition metal ions. The glass is the source and the reactive medium for the growth of nanoparticles. Doped glass with ions copper enable the synthesis and the immobilization of copper nanoparticles (CuNPs). In the sense, the objective of this work was to synthesise and characterize the doped borophosphate glasses with different concentrations (3, 6, 9 and 12 mol%) of Cu+ ions. Moreover, the appplication of the glasses as an “in situ” growth of CuNPs by reaction of the glass with borohydride ions, and its performance in the p-nitrophenol catalytic reduction. Furthermore, we propose a mathematical model that can describe the whole p-nitrophenol reduction reaction process. The glass was obtained by the fusion/cooling method and characterized by infrared spectroscopy (FTIR), Raman spectroscopy, differential thermal analysis, X ray diffraction (XDR) and inductively coupled plasma optical emission spectrometry (ICP-OES). The confirmation of CuNPs formation onto vitreous sample was performed by UV-Vis and XDR spectroscopy techniques. The kinetics of the p-nitrophenol reduction reaction was monitored by UV-Vis spectroscopy. The results showed that the borophosphate glass matrix with high concentration of Cu+ ions (12 mol%) was more efficient of reduction p-nitrophenol in the kinetics. Moreover, a lower induction time was noticed for this concentration of copper ions into glass matrix (i.e., with an increased initial concentration of copper ions in the glass matrix, was the gradual reduction of the induction time). Additionally, kinetic tests were carried out varying the particle size of the catalyst with four size ranges. Thus, the most efficient kinetics, with a kapp of 1.61 min-1 and without observable induction time, was observed for the smaller sized glass particles with the concentration of copper in the glass matrix of 12 mol%. Moreover, the glass catalyst reuse was evaluated which showed a higher efficiency with successive uses, and it can be applied for six times. Finally, four mathematical models have been proposed to describe the p-nitrophenol catalytic reduction process. Among the models presented, the best fit to the experimental data was based on the Langmuir-Hinshelwood kinetic mechanism associated to a semi-empirical growth rate of the CuNPs in the glass matrix.